IMPLEMENTASI MANAJEMEN PEMASARAN SYARIAH DALAM MENJALANKAN MARKETING YANG BAIK - Sari, Ike Meilinda; Fasa, Muhammad Iqbal; Suharto, Suharto (STAI Darul Qalam Tangerang, 2024)
Marketing is part of the main activities that need to be carried out by companies, both service and goods companies in an effort to maintain the viability of their business. This is because marketing is one of the company's activities, which is directly related to consumers. Implementation of marketing management is necessary, because the more advanced a country is, many can commit fraud if it is not balanced with the existence of sharia. This study aims to reduce unwanted things in marketing in Indonesia due to lack of knowledge about the importance of good marketing management. This research uses descriptive method. The results show that the implementation of marketing management is needed because there are many things that need to be known.